Metaphysics and transcendence - Gibson, Arthur, 1943- (Routledge studies in religion., 2003)
This author presents new metaphysics with a genealogy based on counter-intuition and locates counter-intuition and complexity at the foundations of truth. This book stimulates future philosophical and religious discussion.